Kedudukan Negara Palestina Perspektif Siyasah Dusturiyah - Salsabila Tahal, Andi Aulia Fajjiria (Prodi Hukum Tata Negara Fakultas Syariah dan Hukum Universitas Islam Negeri Alauddin Makassar, 2025)
This study aims to discuss the Siyasah Syar'iyyah review of the establishment of the State of Palestine. This type of research is qualitative research. The research design is library research. The results of the study show that Israeli military aggression against Palestinians requires protection, one of which is from the state. This is one of the pieces of evidence that shows the importance of the existence of a sovereign state. The establishment of the State of Palestine is urgent, one of which is to provide protection for Muslims living in Palestine. This shows that there are benefits. It is an indicator of alignment with Siyasah Syar'iyyah.